Whole blood manganese concentrations in dogs with primary hepatitis. (5th March 2014) - Kilpatrick, S.; Jacinto, A.; Foale, R. D.; Tappin, S. W.; Burton, C.; Frowde, P. E.; Elwood, C. M.; Powell, R.; Duncan, A.; Mellanby, R. J.; Gow, A. G.
<x xml:space="preserve">Abstract</x> Objectives Increased whole blood manganese concentrations have been reported in humans with primary liver disease. Due to the neurotoxic effects of manganese, altered manganese homeostasis has been linked to the development of hepatic encephalopathy. Whole blood manganese concentrations are increased in cases of canine congenital portosystemic shunts, but it remains unclear whether dogs with primary hepatopathies also have altered manganese homeostasis. Methods Whole blood manganese concentrations were measured by graphite furnace atomic absorption spectrometry in 21 dogs with primary hepatitis, 65 dogs with a congenital portosystemic shunt, 31 dogs with non‐hepatic illnesses and 18 healthy dogs. Results The whole blood manganese concentrations were significantly different between dogs with primary hepatitis, dogs with non‐hepatic illnesses and healthy dogs (P=0·002). Dogs with primary hepatitis had significantly increased whole blood manganese concentrations compared with healthy dogs (P<0·05) and dogs with non‐hepatic illnesses (P<0·01). Dogs with primary hepatitis had significantly lower whole blood manganese concentration compared with dogs with congenital portosystemic shunts (P=0·0005). Clinical Significance Dogs with primary hepatopathies have increased concentrations of whole blood manganese although these concentrations are not as high as those in dogs with congenital portosystemic shunts. The role of altered manganese homeostasis in canine hepatic encephalopathy is worthy of further study.